Carbon footprint analysis of student behavior for a sustainable university campus in China. (1st November 2015) - Li, Xiwang; Tan, Hongwei; Rackes, Adams
Abstract: Sustainable urban design, systems-level organizational planning, and human behavior have all been recognized for their potentially important roles in helping to reduce energy costs and associated environmental impacts, including greenhouse gas emissions. University campuses, with their long planning timeframes, centralized organizations, and dense populations, are ideal places to examine these carbon mitigation strategies. In this study, we developed a novel methodology for estimating an average student's personal carbon footprint and deployed it at a university in Shanghai. Given the scarcity and uncertainty of existing information, we created and administered an online structured survey to capture students' energy consumption patterns, behavioral tendencies, and willingness to engage in energy conservation. Survey responses, combined with utility data and emissions calculations, indicated that the average annual carbon footprint was a relatively modest 3.84 tons of CO2 equivalent per student, with 65% attributable to daily life, 20% to transportation, and 15% to academic activities like studying. The top three individual uses were dining (34%), showering (18%), and dorm electricity loads (14%). Men, graduate students, and students from metropolitan areas had higher footprints than women, undergraduates, and students from rural areas and small towns. Communal activities like dining in the dining halls, showering in communal showers, and studying in the library were all observed to lead to lower carbon footprints. These analyses can help identify student behavior changes that will be most effective at reducing aggregate carbon emissions. Awareness campaigns may be effective, given that 87% percent of respondents said they engaged in energy saving behavior, but only 22% reported turning off electronics when not in use. Survey responses and carbon footprint calculations were also used to identify actions the university could take to reduce emissions, both now and in terms of upgrades as the campus develops and Chinese living standards continue to rise. Highlights: College student energy behaviors are surveyed and analyzed. A modified carbon footprint model has been developed for college students. College student GHG emission reduction potentials are identified. Campus sustainable improvement scenarios are evaluated and recommended.